After bleaching enamel remineralization using a bioactive glass-ceramic (BioSilicate) - Rastelli, A. N.S. [UNESP]; Nicolodelli, G.; Romano, R. A.; Milori, D. M.B.P.; Perazzoli, I. L.O.; Ferreira, E. J.; Pedroso, A. C.B. [UNESP]; Souza, M. T.; Peitl, O.; Zanotto, E. D. (Portico, 2016)
Tooth bleaching agents may weaken the tooth structure, therefore, it is important to minimize any risks of enamel and dentine damage caused by them. In this way, different materials have been used to avoid or minimize the tooth damage during bleaching. Recently, bioactive glasses have been demonstrated to be effective in mineralization of dental structures. Therefore, this study evaluated the effect of BioSilicate (a polycrystalline bioactive glass-ceramic) after bleaching by Laser-induced breakdown spectroscopy (LIBS) technique. Bovine dental blocks with 4 4 3 mm were obtained (n = 20), sequentially embedded in epoxy resin and then polished. Bleaching was performed using 35% hydrogen peroxide (Whiteness HP). Calcium (Ca) and phosphate (P) intensity values by LIBS were obtained before the treatment (T0, baseline - control Group), after bleaching (T1), and after BioSilicate application (T2). The use of BioSilicate after bleaching showed to be an optimal way to remineralize enamel surface making BioSilicate application a promising adjunct step to avoid or minimize the mineral loss on enamel surface after bleaching.
Keywords: BioSilicate; Dental enamel; Hydrogen peroxide; Mineral loss; Remineralization; Spectroscopy; Tooth bleaching